Report of chronic myeloid leukemia in chronic phase from Eastern India, Institute of Hematology and Transfusion Medicine, Kolkata, 2001-2009 - Siddhartha Sankar Ray; Prantar Chakraborty; Utpal Chaudhuri; Ganesh (Indian Journal of Medical and Paediatric Oncology)
The data 192 patients from Eastern India, Kolkata center was presented in Indian cooperative oncology network meeting, out of which 97% patients were diagnosed in the chronic phase. Complete hematological response was seen in 70.5% among patients and 86% of patients were in clinical and hematological remission over 5 years with a median follow-up of 4.85 years.